2011
DOI: 10.5114/aoms.2011.20609
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the erythrocyte plasma membranes in patients with alcohol-induced liver cirrhosis – preliminary results

Abstract: IntroductionConformations of membrane proteins, membrane fluidity of erythrocytes in patients with AILC were studied with the use of electron paramagnetic resonance and spectrophotometric methods. The concentration of substances reacting with thiobarbituric acid was also determined. The aim of the study was to recognize the nature, level and causes of changes in the structure of erythrocytary membrane observed in erythrocytes of patients compared to erythrocytes from healthy controls.Material and methodsSpin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Our results found that the percentage of PS exposure on BCs progressively increased with Child–Pugh category. Previous studies showed that cirrhotic patients have higher levels of activated platelets and have erythrocytes with changed morphology and shorter life span, supporting our results . PS exposure on BCs from healthy subjects cultured with cirrhotic serum was significantly higher than when cells were cultured in normal serum, indicating that BCs may be activated or injured by toxic substances in cirrhotic serum (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our results found that the percentage of PS exposure on BCs progressively increased with Child–Pugh category. Previous studies showed that cirrhotic patients have higher levels of activated platelets and have erythrocytes with changed morphology and shorter life span, supporting our results . PS exposure on BCs from healthy subjects cultured with cirrhotic serum was significantly higher than when cells were cultured in normal serum, indicating that BCs may be activated or injured by toxic substances in cirrhotic serum (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…We also studied influence of tannins on physical state of erythrocyte membrane by EPR method. The use of fatty acids with different position paramagnetic groups as EPR probes allows to monitors changes in membrane structure at various depth (Sonmez et al 2013 ; Ajdzanovic et al 2010 , 2011 , 2015 ; Mendanha et al 2013 ; Gwozdzinski et al 2011 ). We have chosen 5-DS because tannins with big molecular mass are known to affect the membrane surface without causing significant changes in the depth of the bilayer (Olchowik et al 2012 ; Tarahovsky 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with MHE had significant difficulties in various aspects of their lives, including social activities, emotions, sleep and work [ 4 6 ]. Thus, early detection and treatment of MHE, especially among cirrhotic patients, bear significant implications for the clinical and research societies [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%